(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The article describes the process of three symbolic chartings of an influential book by Rebecca West Black Lamb and Grey Falcon. A Journey through Yugoslavia. The first, anti-colonial charting of the book took place in Great Britain and the USA in 1941/42 (during World War Two), following its publication. The second charting took place in the Western countries during the secession wars in Yugoslavia in the 1990s, from the colonial point of view. The third charting is only to be expected given the publication of an integrated translation of West’s book into Serbian in 2004. The envisioned process of a new, post-colonial reading of her text from the position of different post-Yugoslav nations could be intellectually and politically reinvigorating one.